Degradation control for electric vehicle machines using nonlinear model predictive control - Samaranayake, Lilantha; Longo, Stefano (IEEE, 2017)
Electric machines (motors and generators) are over actuated systems. In this paper, we show how to exploit this actuation redundancy in order to mitigate machine degradation while simultaneously ensuring that the desired closed loop performance is maintained. We formulate a multiobjective optimization problem with a cost function having terms representing closed loop performance and component degradation for an inverter-fed permanent magnet synchronous motor. Such machines are important as they are widely used as the prime mover of commercial electric vehicles. The resulting optimal control problem is implemented online via a nonlinear model predictive control (NMPC) scheme. The control framework is validated for standard vehicle drive cycles. Results show that the NMPC scheme allows for better closed loop performance and lower degradation than standard industrial controllers, such as the field-oriented control method. Hence, this paper demonstrates how the remaining useful life of a machine can be increased by appropriate controller design without compromising performance.
Keywords: Degradation; Torque; Electric machines; Integrated circuit modeling; Cost function; Vehicle dynamics; Optimal control; Nonlinear model predictive control (NMPC); Permanent magnet synchronous motor (PMSM)